2018
DOI: 10.1542/peds.2017-3616
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent E-Cigarette, Hookah, and Conventional Cigarette Use and Subsequent Marijuana Use

Abstract: OBJECTIVES: Noncigarette tobacco products may confer a risk of marijuana use similar to combustible cigarettes. We examined whether adolescent electronic cigarette (e-cigarette), hookah, or combustible cigarette use is associated with initiating and currently using marijuana as well as using both tobacco and marijuana concurrently. METHODS:Adolescents from 10 public schools in Los Angeles, California, completed in-classroom surveys at baseline (fall 2013, ninth grade) and at a 24-month follow-up (fall 2015, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
80
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 38 publications
5
80
1
2
Order By: Relevance
“…1,2 This finding is important because the short-and long-term health impact of adolescent e-cigarette use is more harmful than we think. 1,2 Meanwhile, the industry, the tobacco research community, and online information are promoting the e-cigarette as a less harmful tobacco cessation tool. E-cigarette use is also promoted in the most recent science and technology report by the UK government.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…1,2 This finding is important because the short-and long-term health impact of adolescent e-cigarette use is more harmful than we think. 1,2 Meanwhile, the industry, the tobacco research community, and online information are promoting the e-cigarette as a less harmful tobacco cessation tool. E-cigarette use is also promoted in the most recent science and technology report by the UK government.…”
mentioning
confidence: 91%
“…According to a recent study published by Audrain-McGovern et al, 1 electronic cigarette (e-cigarette) use and the risk of initiating marijuana use is 3.63 times higher among current adolescent e-cigarette users (odds ratio 3.63; 95% confidence interval 2.69-4.90). 1 Accumulating evidence suggests that e-cigarette use is a risk factor for future transition to the use of marijuana. 1,2 This finding is important because the short-and long-term health impact of adolescent e-cigarette use is more harmful than we think.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…profiles of subsequent substance use, Suftin et al 15 found that those who initiated with cigarettes or cigar products were more likely to be current cigarette smokers compared to those who initiated with ATPs 15 . Other research has indicated that first using cigarettes increased the likelihood of initiating marijuana by four times 17 . Additionally, those who initiated with smokeless tobacco were twice more likely to initiate cigarettes and more likely to be dual or poly tobacco users 15 .…”
Section: Introductionmentioning
confidence: 97%
“…For example, experimenting with e-cigarettes may increase risk of initiating cigarette use 18,19 , and experimenting with hookah may increase the risk of using combustible tobacco products and e-cigarettes 20 . In addition, e-cigarette or hookah use has been associated with higher risk of initiating marijuana use 17 . Moreover, marijuana use during adolescence and young adulthood is associated with increased risk of tobacco initiation 21 .…”
Section: Introductionmentioning
confidence: 99%